Thick-Anchored Dual-Layer Locking Supporting Technique in Gob-Side Entry Driving with the Narrow Pillar: A Case Study. (21st December 2022) - Han, Changliang; Yuan, Yuxin; Zhang, Nong; Zhao, Yi; Zhang, Qisheng; Song, Kai; Wei, Min; Guo, Yuxin
Abstract : Roadway maintenance of the gob-side entry driving with narrow pillars is a key issue that needs to be considered in underground mining. In this paper, a thick-anchored dual-layer locking (TADL) supporting technique is proposed, in which, the flexible bolt and the cable are used as the main bodies of the foundation supporting layer and the deep reinforcement layer, respectively. In the instantaneous deformation stage after excavation, TADL is applied to form a thick-anchored bearing structure in time, aiming to achieve the following effects: (1) prevent the delamination of the roadway at the initial stage of excavation, (2) avoid the reduction of the bearing capacity of the surrounding rock structure, and (3) effectively control the plastic zone development and surrounding rock deformation of roof strata. Finally, the mining conditions of gob-side entry driving with narrow pillars are selected for engineering application and verification. The results of numerical simulation and field industrial tests show that the TADL support technique can effectively control the deformation of surrounding rock and drive away tensile stress. Compared with the original support scheme, the roof displacement of the roadway is significantly reduced by more than 16% after TADL support. This study provides a reference for the stability control of roadway roofs under similar conditions.